Knowledge, attitude and practice regarding menstrual cup among adolescent girls in Savadatti taluka, Belagavi district, Karnataka - Shweta Amarappanavar; Arathi P. Rao (International Journal Of Community Medicine And Public Health, 2026)
Background: Menstrual hygiene management (MHM) is a vital component of adolescent health. Despite being safe, reusable, and eco-friendly, menstrual cups are underutilized in India due to cultural taboos and lack of awareness. This study assessed the knowledge, attitude, and practices (KAP) regarding menstrual cup use among adolescent girls. Methods: A community-based cross-sectional study was conducted from January to June 2025 among adolescent girls aged 15–19 years from 10 schools and 5 colleges, selected through multistage random sampling. Data were collected using a pre-tested, semi-structured questionnaire and analysed using descriptive statistics and Chi-square tests. Results: Among 426 participants, 43.9% were aware of menstrual cups, yet only 21.1% had adequate knowledge and 9.2% reported use. Positive attitudes were observed in 43.7%. Social media and the internet were the most common sources of information (39.6%), followed by family/friends (24.1%), healthcare professionals (18.7%), teachers (10.2%), and advertisements (7.5%). Knowledge was significantly associated with age, residence, and family income (p